2022
DOI: 10.3390/ani12202873
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Molecular Characterization of Enteric Viruses in Poultry Flocks in Hebei Province, China

Abstract: Enteric viruses, as a potential pathogen, have been found to be vital causes of economic losses in poultry industry worldwide. The enteric viruses widely studied to date mainly include avian nephritis virus (ANV), avian reovirus (ARe), chicken astrovirus (CAstV), chicken parvovirus (ChPV), fowl adenovirus group I (FAdV-1), infectious bronchitis virus (IBV), and avian rotavirus (ARoV). This paper aimed to identify single and multiple infections of the seven enteric viruses using the data obtained from positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…According to previous studies, multiple enteric viral infections are detected regularly, causing substantial financial losses in poultry industry worldwide ( Kaithal et al, 2016 ; De la Torre et al, 2018 ; Chen et al, 2022 ). For example, the molecular examination of seven enteric virus of commercial chicken flocks in Brazil between 2010 and 2017 showed that 86.3% samples were positive for a single virus, and the remaining 13.7% were found in multiple infections ( De la Torre et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous studies, multiple enteric viral infections are detected regularly, causing substantial financial losses in poultry industry worldwide ( Kaithal et al, 2016 ; De la Torre et al, 2018 ; Chen et al, 2022 ). For example, the molecular examination of seven enteric virus of commercial chicken flocks in Brazil between 2010 and 2017 showed that 86.3% samples were positive for a single virus, and the remaining 13.7% were found in multiple infections ( De la Torre et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the molecular examination of seven enteric virus of commercial chicken flocks in Brazil between 2010 and 2017 showed that 86.3% samples were positive for a single virus, and the remaining 13.7% were found in multiple infections ( De la Torre et al, 2018 ). In addition, the detection and molecular characterization of seven enteric virus in poultry flocks in China indicated that 73.1% samples were single infection, multiple infections were identified in the remaining 26.9%, as well as 69% ChPV was single infection, whereas ANV (61.4%) and CAstV (56.1%) were multiple infections ( Chen et al, 2022 ). According to the current epidemiological investigation, co-infections of CAstV with ChPV or ANV were also detected frequently, and 61.3% of CAstV was related to a single infection, whereas ChPV (22.6%) and ANV (16.1%) were co-infected with CAstV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of RSS in poultry has been described as possibly being related to infection by one or more poultry enteroviruses, including poultry parvovirus, CAstV, AvRV, picornavirus, avian reovirus (ARV), and infectious bronchitis virus (IBV) [ 9 , 10 , 11 , 18 , 19 , 20 ]. ChPV has been detected in chickens with RSS in a few countries, such as India, Brazil, Korea, Poland, and China [ 21 , 22 , 23 , 24 , 25 ]. Zsak et al [ 4 ] and Nuñez et al [ 26 ] showed that SPF chicks infected with ChPV exhibit obvious clinical symptoms of RSS.…”
Section: Introductionmentioning
confidence: 99%